2020
DOI: 10.1177/1071181320641251
|View full text |Cite
|
Sign up to set email alerts
|

Public Trust and Acceptance for Concepts of Remotely Operated Urban Air Mobility Transportation

Abstract: There is building interest within industry and government to enable Urban Air Mobility (i.e., air-taxies). One concept envisions remotely piloted aircraft, yet it is unclear how this will impact public trust and acceptance. Method: Two hundred participants read vignettes describing remotely-piloted UAM operations and then responded to a series of questionnaires. The study employed a one-way between-subjects design manipulating five levels of Pilot-in-Command Distance: Onboard Pilot; Remote Control Pilot; Dedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Adding to these results, statistical research suggest that respondents' feelings of safety towards eVTOLs strongly depend on how it is piloted. Chancey and Politowicz show in their study design that the willingness to use remotely piloted pUAM services is lower compared to services with an on-board pilot, as the latter is trusted more [62]. Similar results can be found regarding the future potential for fully automated [60] or autonomous [59] eVTOL operation in passenger transportation respectively.…”
Section: Perceived Safetysupporting
confidence: 55%
“…Adding to these results, statistical research suggest that respondents' feelings of safety towards eVTOLs strongly depend on how it is piloted. Chancey and Politowicz show in their study design that the willingness to use remotely piloted pUAM services is lower compared to services with an on-board pilot, as the latter is trusted more [62]. Similar results can be found regarding the future potential for fully automated [60] or autonomous [59] eVTOL operation in passenger transportation respectively.…”
Section: Perceived Safetysupporting
confidence: 55%
“…A case study on the Dallas-Fort Worth area showed that a higher percentage of the respondents indicated that they would not prefer to board the automated/non-piloted aircraft [20]. Another study also showed similar results, whereby public acceptance of UAM was found to be negatively affected by remote pilots/operators, as compared to having pilots onboard [37].…”
Section: Identified Gapsmentioning
confidence: 87%
“…However, the use of UAVs in urban areas is a significant concern in terms of public acceptance (Al-Dosari & Fetais, 2023;Lee, Hess, & Heldeweg, 2022). Studies have highlighted that the greatest challenge in this regard is the acceptance of the system by public (Chancey & Politowicz, 2020;Cohen, Shaheen, & Farrar, 2021;Janotta, Peine, & Hogreve, 2021;Kim, Lim, & Ji, 2023;Stolz & Laudien, 2022). While UAVs present an opportunity to increase transportation capacity in densely populated metropolitan areas, their successful integration into existing transportation systems is heavily reliant on public acceptance (Johnson, Miller, & Conrad, 2022).…”
Section: Literaturementioning
confidence: 99%
“…Currently, there are not enough studies that fully explain why people would or would not use UAVs . Studies have shown that understanding the people's perspective on UAVs, which will impact urban transportation worldwide, is crucial for the successful implementation of UAM (Al Haddad et al, 2020;Chancey & Politowicz, 2020;Silva et al, 2023).…”
Section: Introductıonmentioning
confidence: 99%